Evaluation of Immunity to Measles and Varicella (Chickenpox) Viruses in Children and Adolescents of the Páez Municipality, State of Zulia, Venezuela - Jennifer Gotera; Alibeth Mavárez; José Hernández; Florencio Añez; Alegría Levy; Anyelo Duran; Yraima Larreal; Mery Maldonado; Luz Espina; Nereida Valero (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
Exanthematic diseases are a group of pathologies caused by viral agents, which appear frequently during the first years of life and respond in greater proportion to infections caused by viruses, such as measles, varicella (chickenpox), rubella (German measles) and dengue, among others. The objective of this study is to evaluate immunity to measles and chickenpox viruses in children and adolescents residing in the Páez municipality, state of Zulia, Venezuela. Without regard to sex, 174 samples from apparently healthy adolescents and children between 8 and 17 years old were studied and analyzed using the ELISA technique. A frequency of 59.7% was detected for the measles virus and 44.8% for varicella. Seroprevalence for measles and varicella was distributed homogeneously in all age groups. For both diseases, greater frequency was observed in males, without significant differences. The study demonstrated low immunity to these viruses and suggests increasing vaccination programs in this municipality to eliminate circulation of these infectious agents in the population.